Hispanic-serving institution lobbyists: the influence of formative experiences on college-access policy discussions - Heredia-Griego, Meriah E., author; Anderson, Sharon, advisor; Davies, Timothy, committee member; Sagás, Ernesto, committee member; Sierra, Christine, committee member (Colorado State University. Libraries, 2013)
Lobbyists are increasingly a central part of the administration at higher-education institutions. The purpose of this study was to explore the formative life experiences, regarding race and racism, of lobbyists for Hispanic Serving Institutions (HSIs)-institutions with 25% or more Hispanic student enrollment-and how those lobbyists discussed access to higher education for undocumented students. The study describes how the participants constructed identities for themselves and undocumented students in a policy discussion, and it describes the role of HSIs in this timely policy discussion. To accomplish these goals, I used a qualitative research design that integrates elements of narrative inquiry and case study. I used holistic content analysis and dialogic/performance analysis to understand the relationship between formative life experiences and policy discussions. Additionally, descriptive and substantive representation theories provide a framework for critiquing the representation of undocumented students in HSI lobbying efforts. This first-of-its-kind case study informs lobbyist hiring practices, lobbying behaviors, policy discussions, and alignment of institutional values with lobbying initiatives at HSIs.
Keywords: narrative; dialogic performance; education lobbyists; government relations; Hispanic serving institutions; identity construction